Penerapan Metode Lean Six Sigma (DMAIC) untuk Meningkatkan Produktivitas Plat Silinder di PT. X - Kusuma, Fadyla Indra; Halim, Hafidz Akbar; Hidayat, Ade Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. X is a manufacturing company that produces fire extinguishers (APAR), where cylindrical plate welding is a critical process. However, the process is often inefficient due to several non-value-added steps. This study aims to improve welding productivity using Lean Six Sigma through the DMAIC (Define, Measure, Analyze, Improve, Control) approach and by measuring Overall Equipment Effectiveness (OEE). The initial OEE value was 67.49%, far below the world-class standard of 85%. Pareto analysis showed the highest downtime was due to cycle time issues, especially during setup and cutting of additional plates. Improvements were made by eliminating the cutting process and adding a stopper to ensure accurate welding positions. These changes reduced the cycle time from 180 seconds to 120 seconds and increased the OEE to 76.12%.